Impeding the single-strand annealing pathway of DNA double-strand break repair by withaferin A-mediated FANCA degradation - Liu, Wenjun (DNA Repair (Amst), 2019)
FANCA is a key player in the canonical Fanconi anemia (FA) repair pathway. We have recently shown that FANCA also plays an important role in the single-strand annealing sub-pathway (SSA) of DNA double-strand break (DSB) repair by biochemically catalyzing single-strand annealing. Here, we report that a steroidal lactone withaferin A (WA) specifically impedes SSA repair by promoting FANCA downregulation at a sub-micromolar concentration range. We find that WA causes FANCA downregulation post-translationally in a proteasome-dependent manner. This WA-mediated downregulation is achieved through HSP90 inhibition and disruption of the FANCA-HSP90 interaction. WA-mediated FANCA degradation significantly reduces cellular SSA repair, abolishes FANCD2 monoubiquitination, elevates sensitivity to mitomycin C, and results in accumulation of DSBs. Importantly, the WA-induced defect in SSA repair is highly dependent on the absence of FANCA protein and overexpression of exogenous WT-FANCA protein in WA-treated cells significantly complements the repair defect.